Ears to the ground: how politicians in India learned what voters wanted, 1967-1971. Issue 3 (26th May 2020) - Kushner, Daniel
ABSTRACT: How do politicians learn what their voters want? This article explores how Indian politicians leverage different types of interlocutors in order to develop coherent perspectives of voter wants to support policy and strategy development. It then uses innovative archival data to demonstrate how access to different types of interlocutors made key political developments possible.